Síndrome de Burnout y su incidencia en el personal médico del Hospital José Antonio Vargas: Burnout syndrome and its incidence in the medical staff of the José Antonio Vargas hospital (La U Investiga, 2018)
The abstract is the translation of the summary of its publication in an alternative language, for the case of the magazine the U Investiga is the English. Therefore, it must be consistent and precise, as well as its summary.The burnout syndrome is a response to chronic job stress, composed of negative attitudes and feelings towards people with whom (attitudes of depersonalization) work, the professional role (lack of professional fulfillment at work) itself and also by the experience of being emotionally drained (Gil-Monte & Peiró, 1997).Therefore the burnout syndrome has great relevance in areas and various occupational groups. The initial scans were performed in physicians and nurses (I) subsequently professionals linked to mental health such as psychiatrists, psychiatric and auxiliary nurses of Nursing (Gil-Monte & Peiró, 1997 The main objective of the research was included was a comparative study on burnout syndrome and its impact on job performance in hospital doctors Jose. Antonio. Vargas located in Palo Negro Edo Aragua. this report was aimed under investigation and type correlational and descriptive. the study population consisted by resident physicians and specialists who work in the various departments of IVSS Jose. A. Vargas. the sample consisted of 37 medical residents and specialists without age range, who applied a questionnaire of 15 questions scale lickert type. for reliability a pilot test where the results of that test was applied were subjected to a reliability matrix to obtain the reliability index by Alfa Cronbach where a value of 0.91 was obtained; which allowed us to establish the high reliability of the instrument. The information collected was processed through quantitative techniques in which the frequency and statistical percentage qualitative analysis was determined. The results show that if there is a presence of burnout syndrome than 70% in the institution which has its effects on workperformance.
Keywords: of bournout syndrome; patient; medical; stress; exhaustion